2020
DOI: 10.12659/msmbr.924203
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Alzheimer’s Disease Molecular Mechanism of Acori Tatarinowii Rhizoma Based on Network Pharmacology

Abstract: Background:Acori Tatarinowii Rhizoma (ATR), a traditional Chinese herbal medicine, is used to treat Alzheimer's disease (AD), which is a worldwide degenerative brain disease. The aim of this study was to identify the potential mechanism and molecular targets of ATR in AD by using network pharmacology. Material/Methods:The potential targets of the active ingredients of ATR were predicted by PharmMapper, and the targets of Alzheimer's disease were searched by DisGeNET. All screened genes were intersected to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It also ameliorated Aβ1–42-induced neuro-inflammation in BV-2 microglial cells through the suppression of TLR4, NO, PGE2, iNOS, and COX-2 expression, and the secretion of pro-inflammatory cytokines [ 96 ]. Recently, Zhang and colleagues [ 280 ] have shown that BCP may protect SH-SY5Y cells against Aβ neurotoxicity via the inhibition of JAK2 expression. BACE1 protein is crucial for the synthesis of amyloid precursor protein (APP).…”
Section: Neuroprotective Potential Of β-Caryophyllene and Carnosic Ac...mentioning
confidence: 99%
“…It also ameliorated Aβ1–42-induced neuro-inflammation in BV-2 microglial cells through the suppression of TLR4, NO, PGE2, iNOS, and COX-2 expression, and the secretion of pro-inflammatory cytokines [ 96 ]. Recently, Zhang and colleagues [ 280 ] have shown that BCP may protect SH-SY5Y cells against Aβ neurotoxicity via the inhibition of JAK2 expression. BACE1 protein is crucial for the synthesis of amyloid precursor protein (APP).…”
Section: Neuroprotective Potential Of β-Caryophyllene and Carnosic Ac...mentioning
confidence: 99%
“…SCI-induced secondary damage leads to further neuronal cell loss by apoptosis cell death mediated by intracellular caspase proteases [ 8 ]. Activating the caspase-3 proenzyme triggers the death of nerve cells in SCI during the chronic phase [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%